(untitled) (Research, Society and Development, 2021)
The objective of this article is to verify how violence against the elderly manifests itself in the city of Manaus, capital of the State of Amazonas and in the State of Amazonas. This is a descriptive study based on a documentary survey, through which the categories of violence / crimes and the numbers of violence suffered by the elderly are identified after the enactment of Law No. 12,461 / 11, which amended article 19 of Statute of the Elderly. For the analysis of the situation in Manaus, the data provided by the Statistics Department, of the Intelligence Department of the State Secretariat of Public Security of Amazonas (SSP / AM), was used as a source of information, in the historical series from the year from 2012 to 2019 and for the information on the State of Amazonas, in the same period, the statistical data from the Human Rights Service, the Dial 100 service, was used. The results show that in Manaus there was a linear increase in violence against the elderly while in Amazonas, the data points to an oscillation in the number of records. In comparison to other states, Amazonas stands out as one of the most violent states in the country. The increase in the number of cases may result both from the increase in violence against the elderly, but also from the knowledge and use of the various reporting channels that exist today, especially the possibility of anonymous reporting, made possible through Disk 100. The article ends by pointing out a worrying picture reinforcing the challenges imposed today.